A Rapid and Simple High-Performance Liquid Chromatographic Method for Determination of Levofloxacin in Human Plasma - Dion Notario; Sudibyo Martono; Zullies Ikawati; Arief Rahman Hakim; Fathul Jannah; Endang Lukitaningsih (Universitas Gadjah Mada, 2017)
A simple and rapid high-performance liquid chromatography method was developed and validated for quantifying LEV in human plasma. Chromatographic separation was performed under isocratic elution on a Luna Phenomenex® C18 (150 × 4.6 mm, 5 µm) column. The mobile phase was comprised of acetonitrile, methanol, and phosphate buffer 25 mM pH 3.0 (13:7:80 v/v/v) and pumped at a flow rate of 1.5 mL/min. Detection was performed by UV detector at a wavelength of 280 nm. Samples were pre-treated with acetonitrile followed by centrifugation, evaporation, and reconstitution step. The method proved linear (r = 0.995), sensitive (LLOQ and LOD was 1.8 and 0.6 µg/mL respectively), accurate (% error above LLOQ ≤ 12% and LLOQ ≤ 20%), precise (RSD ≤ 9%), robust in the ranges of 1.8-28.8 µg/mL, rapid (separation time not more than 10 min), and simple (use no organic additive in mobile phase). The method was showed reliable for quantifying LEV in human plasma.